The Moderating Role of Social Support in Relationships Self-Disclosure and Loneliness in Adolescents: A Systematic Literature Review - E. Rahim, Amaliah Cindy; Belung, Yulinda Khairunnisa; Karmiyati, Diah (Psikoborneo: Jurnal Ilmiah Psikologi, 2025)
Adolescents are a group that is vulnerable to experiencing feelings of loneliness. Loneliness in adolescents is influenced by two factors: trigger factors and predisposing factors. These are difficulties in establishing social relationships and the neglect of adolescent self-disclosure. This condition suggests that inadequate social interaction and lack of emotional support can increase the risk of loneliness in adolescents. Therefore, it is important to understand and address these factors as essential to supporting the overall health and well-being of adolescents.The aim of this study was to determine whether social support plays an important moderating role in the relationship between self-disclosure and loneliness in adolescents. Systematic Literature Review (SLR) was used as a method to find results showing that social support plays an important moderating role in the relationship between self-disclosure and loneliness in adolescents. The number of journals that have been reviewed is 12 out of 293 after the selection stage was carried out. The study's results showed that social support had a significant role in moderating the relationship between self-disclosure and loneliness. This research provides valuable insights and intervention strategies that can be applied in adolescent education and development to reduce loneliness through increased social support and effective self-disclosure.